Power, patronage, and memory in early Islam - George, Alain; George, Alain; Marsham, Andrew; Marsham, Andrew (Oxford University Press, 2017)
This volume elucidates the ways in which Umayyad elites fashioned and projected their self-image, and how these articulations, in turn, mirrored their own times. The authors, combining perspectives from different disciplines, present new material evidence, introduce fresh perspectives about key themes and monuments, and revisit the nature of the historical writing that shaped our knowledge of this period